2017
DOI: 10.1093/hmg/ddx410
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 phosphorylates membrane-bound Rabs and is activated by GTP-bound Rab7L1 to promote recruitment to the trans-Golgi network

Abstract: Human genetic studies implicate LRRK2 and RAB7L1 in susceptibility to Parkinson disease (PD). These two genes function in the same pathway, as knockout of Rab7L1 results in phenotypes similar to LRRK2 knockout, and studies in cells and model organisms demonstrate LRRK2 and Rab7L1 interact in the endolysosomal system. Recently, a subset of Rab proteins have been identified as LRRK2 kinase substrates. Herein, we find that Rab8, Rab10, and Rab7L1 must be membrane and GTP-bound for LRRK2 phosphorylation. LRRK2 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
273
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 235 publications
(313 citation statements)
references
References 40 publications
38
273
2
Order By: Relevance
“…Our previous experiments, consistent with others [12][13][14] , reveal that a proportion of membrane associated GTP-bound Rab10 protein in transfected cell lines is phosphorylated by LRRK2 in the switch II loop at residue T73, exquisitely dependent on LRRK2 kinase activity in these cells. Consistent with our previous results, immunofluorescence staining using a pT73-Rab10 specific antibody confirmed that pT73-Rab10 signal exclusively localized to vesicular structures, as opposed to total Rab10 signal that can be diffuse (cytoplasmic) and only partially localized to vesicles (Supporting data Figure 4).…”
Section: Lrrk2 Phosphorylates Rab10 On Early Immature Macropinosomessupporting
confidence: 91%
See 3 more Smart Citations
“…Our previous experiments, consistent with others [12][13][14] , reveal that a proportion of membrane associated GTP-bound Rab10 protein in transfected cell lines is phosphorylated by LRRK2 in the switch II loop at residue T73, exquisitely dependent on LRRK2 kinase activity in these cells. Consistent with our previous results, immunofluorescence staining using a pT73-Rab10 specific antibody confirmed that pT73-Rab10 signal exclusively localized to vesicular structures, as opposed to total Rab10 signal that can be diffuse (cytoplasmic) and only partially localized to vesicles (Supporting data Figure 4).…”
Section: Lrrk2 Phosphorylates Rab10 On Early Immature Macropinosomessupporting
confidence: 91%
“…LRRK2-mediated phosphorylation of Rab10 is strongly affected by all known pathogenic mutations as well as PD-risk factor genetic variants like G2385R, with Rab10 phosphorylation changing the affinity of different binding proteins to the Rab10 effector loops 12 . Our past work, suggests LRRK2 phosphorylation of Rab10 may prolong Rab10 in a GTP-bound state by inhibiting Rab10 interactions with GAP proteins 13 . While the specific role of Rab10 in cells linked to neurodegeneration is under investigation, recent work demonstrates Rab10 downregulates ciliogenesis in some types of cells and neurons in the brain 14 .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…54 In cells, RAB29 has been shown to bind LRRK2 to increase TGN-localisation and kinase activity. 15,21,55 Our siRNA screen nominated AP2A1 as a strong modifier of LRRK2 recruitment and showed that depletion of AP2A1 in the presence of RAB29 caused a further increase of LRRK2 autophosphorylation. The mechanism by which this occurs is not yet known.…”
Section: Discussionmentioning
confidence: 99%